Upper-Bound Finite Element Adaptive Analysis of Plane Strain Heading in Soil with a Soft Upper Layer and Hard Lower Layer - Jian Zhang; Li Ding; Yu Liang; Jingyao Zong; Zhenya Li (Advances in Civil Engineering)
This paper investigates the stability of a rectangular tunnel face affected by surcharge loading in soil with a soft upper layer and hard lower layer using upper-bound finite element methods with a plastic-dissipation-based mesh adaptive strategy (UBFEM-PDMA). Seven different positions for the soil interface are selected to study this problem. The upper bounds on the ultimate surcharge loads σs are presented in terms of dimensionless stability charts. The σs increases with tunnel depth, and it increases when the position of the soil interface moves up along the tunnel face. The failure mechanism primarily involves a wedge-shaped zone around the tunnel face and two slip lines originating from the top and bottom of the tunnel face, and it is mainly influenced by three factors, i.e., the position of the soil interface, the soil properties, and the tunnel depth. In contrast to the failure mechanism for uniform soil, multiple slip lines exist in the tunnel face in soil with a soft upper layer and hard lower layer. The results compare reasonably well with those in the literature and those from the numerical method.